The psychology of evolving technology : how social media, influencer culture and new technologies are altering society - Okunev, Rhoda (Apress, 2023)
Technological innovations have advanced at an incredible speed since the introduction of the computer that it has altered the fabric of our society. The possession of computers, smart-devices, along with social media, texting and video games, is now an intimate part of the structure of our culture. This book is a framework to start a conversation on how technology is changing our lifestyles and transforming our world. There is now an entire generation that has been using technology through the most delicate developmental time in their lives. This book presents how to look at the cognitive and psychosocial developmental stages and what are the age-appropriate milestones and factsheet of behaviors at different ages. It provides insight into the strength and vulnerable characteristics at each stage and the prevalence of some negative conditions in our society. You will gain a perspective of the encouraging and challenging aspects of computer learning, smart devices, and how to start and keep the conversation going from infancy to adulthood in order to keep and maintain your virtues and ways to circumvent unfavorable consequences. In short, The Psychology of Evolving Technology looks at how cutting-edge and revolutionary high technologies have disrupted our society through its many luxuries and conveniences and how it has altered the outlook of our values, privileges, and expectations. What You'll Learn Determine what adjustments should be made to regulate new innovations to allow them to succeed See how development stages in a child now interact with technology Review how social media and influencer culture are changing the way we see ourselves in society Who This Book Is For All readers curious about the effect of technology on individuals, growing children, and the fabric of society.